2014
DOI: 10.1039/c3ra44789h
|View full text |Cite
|
Sign up to set email alerts
|

PVDF film tethered with RGD-click-poly(glycidyl methacrylate) brushes by combination of direct surface-initiated ATRP and click chemistry for improved cytocompatibility

Abstract: To enhance the cytocompatibility of polyvinylidene fluoride (PVDF) films, arginine-glycine-aspartic acid (RGD) peptide-click-poly(glycidyl methacrylate) (PGMA) polymer brushes were grafted onto the PVDF surface by the combination of surface-initiated atom transfer radical polymerization (ATRP) and click reaction. The direct initiation of the secondary fluorine atoms of PVDF backbone allowed for grafting of the PGMA brushes containing reactive epoxy groups. Subsequent introduction of the azide groups onto the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 64 publications
6
58
1
Order By: Relevance
“…Upon grafting of PGMA, the surface roughness of PVDF-g-PGMA membrane reveals an obvious increase about 193.12 nm. This result was consistent with the previous findings that the grafting of the PGMA can lead to a significant increase in surface roughness value, as well as surface morphology [67]. After grafting of PVDF-g-PGMA copolymer with PVPA, by increasing the PVPA ratio, it was noticed a considerable decreasing of the surface roughness from 100.05 to 26.73 nm.…”
Section: Atomic Force Microscopy (Afm)supporting
confidence: 94%
See 2 more Smart Citations
“…Upon grafting of PGMA, the surface roughness of PVDF-g-PGMA membrane reveals an obvious increase about 193.12 nm. This result was consistent with the previous findings that the grafting of the PGMA can lead to a significant increase in surface roughness value, as well as surface morphology [67]. After grafting of PVDF-g-PGMA copolymer with PVPA, by increasing the PVPA ratio, it was noticed a considerable decreasing of the surface roughness from 100.05 to 26.73 nm.…”
Section: Atomic Force Microscopy (Afm)supporting
confidence: 94%
“…It is also clear that no cracks were observed which indicates homogeneity of the grafting process. These results confirmed that GMA monomer is grafted onto the PVDF [67][68][69]. After modification of PVDF-g-PGMA copolymer with PVPA, we observed that all samples (Fig.…”
Section: Morphologysupporting
confidence: 92%
See 1 more Smart Citation
“…By contrast, no -OH bending and very weak C-OH peaks were seen in the A12 electrodes, which also had the lowest oxygen content on the surface from XPS analysis. 61,62 After cycling, both inorganic and organic SEI species were identified in the resulting spectra (Figure 6d). Note that all cycled electrodes analyzed here were recovered in an Ar-filled glove box, and the FTIR spectra were also taken inside the glove box to avoid any air exposure.…”
Section: A1842mentioning
confidence: 99%
“…Their results have demonstrated that the immobilization of a specific fibronectin fragments enhanced osteoblast differentiation and improved functional implant osseointegration compared to RGD-functionalized or pristine Ti-substrates. Later on, the same group has decorated [53] Ti-surfaces with another bioactive peptide motif, which also induces [54] have immobilized this peptide sequence on Polyvinylidene fluoride (PVDF) films. These surfaces were initially activated with poly(glycidyl methacrylate) chains using an ATRP polymerization process, starting from secondary fluorine atoms.…”
Section: Polymer Brushes Functionalized With Ecm Peptide/proteinmentioning
confidence: 98%